PHONOLOGICAL STRESS ERRORS IN PAKISTANI ENGLISH AND ITS REMEDIES IN THE LIGHT OF NATIVE PROFICIENCIES - Syeda Bushra Rizvi; Aqsa Sarwar; Amna Rehman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Using the paradigm of supra-segmental phonology, this paper aims at exploring stress patterns of English and Urdu and the resulting difficulties faced by teachers and learners in our class rooms particularly at secondary school level in learning English stress. On the basis of phonological differences between the two languages, the researcher believes that stress patterns of English used in Pakistani class rooms are quite different from those of the native speakers. It carries a tangible impact of Urdu stress pattern with almost equal stress on all the syllables which is quite problematic both for teachers and learners of English whether it is ESL or EFL. Findings of the research provide useful pedagogical insights in the perspectives of English language teaching with particular emphasis on spoken proficiency.